A novel nomogram model based on Ki-67 characteristic expression to predict prognosis in head and neck squamous cell carcinoma - Wang, Tianyi; Xue, Lili; Li, Zhixin; Hong, Zhicong; Hu, Niting; Li, Yi; Yan, Bing (Frontiers in Oncology, 2024)
Objectives This study aimed to examine Ki-67’s correlation with clinicopathological characteristics of head and neck squamous cell carcinoma (HNSCC), evaluate its prognostic significance, and develop a Ki-67 integrated prognostic model. Methods The retrospective study included 764 HNSCC patients hospitalized from 2012 to 2022. Data were sourced from medical records and immunohistochemical analysis of surgical specimens. Results Ki-67 expression was significantly associated with sex, pathological grade, clinical stage, and metastasis, but not with age or recurrence. Higher Ki-67 levels were linked to poorer prognosis, as indicated by Kaplan-Meier survival analysis. Utilizing a Cox proportional hazards model, four prognostic factors were identified: age, recurrence, metastasis, and Ki-67 expression. These factors were used to construct a prognostic model and a nomogram. The model’s predictive accuracy was confirmed by a high concordance index and a reliable calibration curve. Conclusion Ki-67 expression in HNSCC patients correlates with several clinicopathological features and serves as a negative prognostic marker. A prognostic model incorporating Ki-67 was successfully developed, offering a new tool for patient prognosis assessment in HNSCC.